Intraoperative Complications of Cataract Surgery Using Intracameral Illumination in the Elderly over 75 Years. (10th January 2019) - Kim, Yu Jeong; Park, Su Jin; Lee, Jong Yeon; Lee, Dae Yeong; Nam, Dong Heun
Abstract : Purpose . To evaluate intraoperative complications and utilization of adjunctive devices between microscope and intracameral illuminations during cataract surgery in the elderly over 75 years. Design . A retrospective, consecutive, interventional case series Participants. Two hundred eighty-six eyes of 184 patients older than 75 years who underwent cataract surgery using microscope and intracameral illuminations. Methods . A chart review was performed on an advanced cataract surgery group of 141 consecutive cases in which the intracameral illumination was used and on a standard cataract surgery group of 145 consecutive cases in which the intracameral illumination was not used. Main Outcome Measures . Intraoperative complications (posterior capsule rupture, radial tear of the anterior capsule, dropped nucleus, or sulcus-implanted/sclera-fixated IOL) and utilization of adjunctive devices (pupil expansion device or anterior capsule staining). Results . The frequency of use of the pupil expansion device was lower in the advanced cataract surgery group than that in the standard cataract surgery group (0.7% vs 6.9%; p = 0.007 ). Furthermore, the rates of a posterior capsule rupture and at least one intraoperative complication were lower in the advanced cataract surgery group than those in the standard cataract surgery group (0.7% vs 4.8%; p = 0.067 ) (0.7% vs 7.6%; p = 0.004 ). Conclusions . In the current cohort of patients over 75 years, the rate of intraoperative complications was lower when using the intracameral illumination than that when using the conventional method. Cataract surgery using intracameral illumination would be good option for elderly people.